Arctic cinema: War films, detective stories and comedies - I. S. Zonn (Проблемы постсоветского пространства, 2024)
This third article examines such genres of cinema as war films, detectives and comedies the latest in the line of Arctic films. Thereby we draw a line under Arctic films, that have not received due attention from film critics and the public until now. The need to return to the past to take a fresh look at the solar, including its storyboard, taking into account the deep rethinking of the war and the direct depiction of what was experienced, to show a truthful and accurate image of the war on the example of the fate of one or many of its participants. Cinematographers constantly return to the theme of the war, its individual episodes, the people who took part in it, who noted their heroism in it, its new reading caused by changing socio-political views and access to previously censored circumstances, what is now called «trench truth».«Another war» in pleacetime was reflected in the Arctic detectives. The enemy appears in them as criminal elements, sometimes was sophisticated and insidious plans, which in the conditions of the north require a special approach to solve then. Comedies have no geographical boundaries. Humor and laughter in the snow and ice is special, very often associated with the behavior of animals, especially dogs.